2019
DOI: 10.1136/vr.104995
|View full text |Cite
|
Sign up to set email alerts
|

“I don't go to Meetings”: understanding farmer perspectives on bovine TB and biosecurity training

Abstract: In 2016, a veterinary service company, XL Farmcare UK, was awarded a Defra contract to manage a series of on-farm demonstration workshops to raise biosecurity awareness. The workshops provided free training for cattle farmers in England on the practical measures that they could take to limit the threat of bovine tuberculosis (bTB). Despite communicating these events to farmers, the number who subsequently attended them was low and the company decided to conduct research to seek explanation. Farmers were interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, when we consider this and the good explanatory power of the land parcels network metrics, we could speculate that the cattle dataset might hide some contact patterns. This could occur due to the inability to isolate M. bovis in all herd breakdowns or in all cattle, or due to unrecorded movements, with cattle grazing in several land parcels belonging to the same farm but not contiguous to the farm [50,51]. In general, the landscape and the farmland fragmentation and distribution in space, which is ignored when considering farms’ main building locations only, might play a crucial role in disease dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…However, when we consider this and the good explanatory power of the land parcels network metrics, we could speculate that the cattle dataset might hide some contact patterns. This could occur due to the inability to isolate M. bovis in all herd breakdowns or in all cattle, or due to unrecorded movements, with cattle grazing in several land parcels belonging to the same farm but not contiguous to the farm [50,51]. In general, the landscape and the farmland fragmentation and distribution in space, which is ignored when considering farms’ main building locations only, might play a crucial role in disease dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…This paper provides a valuable insight into farmer thinking and opinions on bTB, including the expressed sense of powerlessness and lack of control. In a survey of farmers from Northern Ireland, Hamilton et al ( 24 ) found that farmers felt “utterly powerless and in an intractable position that promoted a sense of despair that paralyzed them and made new learning unappealing and seemingly pointless”. The findings were consistent with Enticott et al ( 25 ) who found that farmers believe they are unable to do anything about bTB but are keen for the government to intervene to help control the spread of bTB.…”
Section: Discussionmentioning
confidence: 99%
“…Skills imparted need to reach the frontline actors where the first contact with pathogens take place. Some trainings at this operational level have not been taken up by the farmers with enthusiasm [ 26 , 27 ]. Trainers of trainers’ programs would ensure continuation of training for longer periods of time sustaining consistent training.…”
Section: Discussionmentioning
confidence: 99%